Modern Methodology of English Language Teaching (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This paper explores the modern methodologies used in English language teaching (ELT). It discusses various approaches such as Communicative Language Teaching (CLT), Task-Based Language Teaching (TBLT), Content and Language Integrated Learning (CLIL), Blended Learning, Flipped Classroom, Collaborative Learning, Differentiated Instruction, and Technology-Enhanced Language Learning (TELL). Each methodology is analyzed in terms of its principles, advantages, and applications in different learning contexts. The paper highlights the importance of adapting teaching methods to meet the diverse needs of learners and the evolving educational landscape.